2010
DOI: 10.1111/j.1365-2486.2009.02049.x
|View full text |Cite
|
Sign up to set email alerts
|

Climatic characteristics of heat waves and their simulation in plant experiments

Abstract: Extreme events such as heat waves are emerging as a key facet of climate change, but to date, experiments on the impacts on plants are scarce. Experimental simulation of heat waves requires knowledge of regional heat wave characteristics, as plant responses depend heavily on meteorological conditions. We analysed nine Western European meteorological datasets, and found that heat waves occurring during the growing season in this region encompass more sunshine ( 1 69%), lower precipitation (À78%) and a larger va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
152
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(158 citation statements)
references
References 52 publications
(65 reference statements)
5
152
0
1
Order By: Relevance
“…As a test, we compared conditions from 15 March-15 October 2003 to normal, and found also here more sunshine, higher temperatures, lower RH and higher VPD, although the anomalies where less outspoken than for the precipitation-free droughts focused on here (data not shown). Warm, sunny and dry conditions also prevailed during heat waves in the same region (De Boeck et al, 2010). This is consistent with a global study by Trenberth and Shea (2005), in which they reported that temperature and precipitation generally co-vary positively in winter and negatively in summer, and should therefore not be interpreted as stand-alone parameters.…”
Section: Meteorological Conditionssupporting
confidence: 77%
See 2 more Smart Citations
“…As a test, we compared conditions from 15 March-15 October 2003 to normal, and found also here more sunshine, higher temperatures, lower RH and higher VPD, although the anomalies where less outspoken than for the precipitation-free droughts focused on here (data not shown). Warm, sunny and dry conditions also prevailed during heat waves in the same region (De Boeck et al, 2010). This is consistent with a global study by Trenberth and Shea (2005), in which they reported that temperature and precipitation generally co-vary positively in winter and negatively in summer, and should therefore not be interpreted as stand-alone parameters.…”
Section: Meteorological Conditionssupporting
confidence: 77%
“…The same cascade also explains why droughts get progressively warmer and sunnier, as we demonstrated. Our finding in a previous study (De Boeck et al, 2010) that heat waves are characterised by significantly less (−78 %) precipitation than normal and that they most often occur after a period of substandard rainfall should be regarded in the same light. New model simulations reinforce the notion of a slow build-up of heat via drought, with heat waves projected to become more intense at the end of summer through progressive soil moisture depletion effects (Fischer and Schär, 2009).…”
Section: Meteorological Conditionsmentioning
confidence: 84%
See 1 more Smart Citation
“…Other studies also confirm the small impact of heat alone on GPP (De Boeck et al, 2010). Only for very long and pronounced extreme events was a clear 5 negative impact on GPP observed (discussed in detail in Sec.…”
supporting
confidence: 63%
“…For example, drought-induced closing of the stomata and the subsequent reduction in evaporative cooling can further increase heat stress when water stress co-occurs with a high temperature anomaly (De Boeck and Verbeeck, 2011;Bréda et al, 2006). Conversely, high temperature impacts can be alleviated 5 by evaporative cooling as long as enough water for transpiration is available (De Boeck et al, 2010).…”
mentioning
confidence: 99%